The Role of Volunteers in Increasing The Accessibility of Drug Abuse Rehabilitation Services through The DESA BERSINAR Application - Febriantika, Febriantika; Cahyati, Widya Hary; Zainafree , Intan (Universitas Negeri Semarang, 2025)
Drug abuse is a complex public health problem in Indonesia. To increase access to rehabilitation services, the government launched the DESA SIAP BERSINAR application as a digital platform that involves volunteers in its implementation. This study aims to analyze the role of volunteers in improving the accessibility of rehabilitation services for people affected by drug abuse through the DESA SIAP BERSINAR application. This study uses a qualitative approach with phenomenological methods. Data was collected through in-depth interviews with volunteers, health workers, and the community involved in the program. Thematic analysis was used to identify key patterns and categories related to volunteer roles. The results of the study show that the Drug Clean Village (BERSINAR) program has a significant impact in increasing the accessibility of community-based rehabilitation services. This program involves Field Line officers and community leaders in providing understanding to the public about the dangers of drugs and the importance of rehabilitation. This activity includes counseling, education, and advocacy directed at high-risk groups. In addition, the program also includes coaching and empowerment for individuals who have participated in rehabilitation services. Recovery Agents in this program play a role in assisting drug users who have undergone rehabilitation so that they can adapt to society again. The psychosocial support provided by recovery agents has been proven to help users in the recovery process as well as prevent them from falling back into drug abuse. Volunteers play a strategic role in expanding the accessibility of rehabilitation services through the DESA SIAP BERSINAR application. More supportive policies and capacity building of volunteers are needed to ensure the sustainability of this program